Tracing the Roots of Prejudices: Perspectives on the Trend of Heinous Portrayal of Disability in Disney Movies and Indian Cinema (International Journal of Food and Nutritional Sciences, 2022)
Disability is an umbrella concept that covers both chronic illnesses, mental and physical impairments. The multidisciplinary field of disability studies is concerned with how people identify and interact with society. The research seeks to re-establish societal fairness and relate to individuals with humanity. Due to the common belief that disabilities are the result of past transgressions and punishments, people with disabilities are typically ostracised and denigrated by society at large. Individuals with impairments receive no respect and are either teased or chastised.